Optimized Tree-Type Cylindrical-Shaped Nanoporous Filtering Membranes with 3 or 5 Branch Pores in Each Pore Tree - Zhang, Yongbin (Current Nanoscience, 2019)
Background: It is necessary to investigate the performances of the optimized tree-type cylindrical-shaped nanoporous filtering membranes with 3 or 5 branch pores in each pore tree. Objective: To explore the design method for and the performances of the liquid-particle and liquidliquid separations of the optimized tree-type cylindrical-shaped nanoporous filtering membranes with 3 or 5 branch pores in each pore tree. Methods: The analysis was made for the flow resistance of the studied membrane based on the nanoscale flow equation. The optimum ratios of the radius of the trunk pore to the radius of the branch pore were typically calculated for yielding the lowest flow resistance of this membrane. The capability of the liquid-liquid separation of this membrane was investigated by exploring the flow resistances of this membrane for different liquids. Results: The optimum ratios of the radius of the trunk pore to the radius of the branch pore were typically calculated for the maximum fluxes of these membranes for different passing liquid-pore wall interactions. They can be used for the design of the studied membranes for liquid-particle or liquid-liquid separations. The flow resistances of the studied membranes in the optimum condition for different liquids were also calculated, and the capability of the liquid-liquid separation of the membranes is evidenced. Conclusion: The obtained results can be used for the design of the studied membranes for achieving their optimum operating condition, by taking the ratio of the radius of the trunk pore to the radius of the branch pore as optimum. The studied membranes also have good capabilities of liquid-liquid separations if the mixed liquids have greatly different interactions with the pore wall and the radius of the branch pore is below 3nm or less.
Keywords: nanopore